2009
DOI: 10.1038/npre.2009.3497.1
|View full text |Cite
|
Sign up to set email alerts
|

Generation of "backbone" free, low transgene copy plants by launching T-DNA from the Agrobacterium chromosome

Abstract: In both applied and basic research, Agrobacterium-mediated transformation is commonly used to introduce genes into plants. We investigated the effect of three Agrobacterium tumefaciens strains and five T-DNA origins of replication on transformation frequency, transgene copy number, and the frequency of integration of non-T-DNA portions of the T-DNA-containing vector ("backbone") into the genome of Arabidopsis thaliana and Zea mays. Launching T-DNA from the picA locus of the Agrobacterium chromosome increases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 0 publications
2
41
0
Order By: Relevance
“…26 Launching of T-DNA from the Agrobacterium chromosome has also been tested for delivery of transgene. 27 This design, which minimizes copy number in Agrobacterium, results in a high percentage of single copy plant transformants with intact T-DNA, although the overall transformation frequency is lower compared to binary vectors. 27 Delivering one long T-DNA from the Agrobacterium chromosome might be a good alternative to the use of several smaller binary vectors.…”
Section: Current Trait Combination Tools: Breeding Stacks and Moleculmentioning
confidence: 98%
See 1 more Smart Citation
“…26 Launching of T-DNA from the Agrobacterium chromosome has also been tested for delivery of transgene. 27 This design, which minimizes copy number in Agrobacterium, results in a high percentage of single copy plant transformants with intact T-DNA, although the overall transformation frequency is lower compared to binary vectors. 27 Delivering one long T-DNA from the Agrobacterium chromosome might be a good alternative to the use of several smaller binary vectors.…”
Section: Current Trait Combination Tools: Breeding Stacks and Moleculmentioning
confidence: 98%
“…27 This design, which minimizes copy number in Agrobacterium, results in a high percentage of single copy plant transformants with intact T-DNA, although the overall transformation frequency is lower compared to binary vectors. 27 Delivering one long T-DNA from the Agrobacterium chromosome might be a good alternative to the use of several smaller binary vectors. However, the additional step of inserting T-DNA into the Agrobacterium chromosome in addition to the reduced transformation efficiency make the method more cumbersome in practice.…”
Section: Current Trait Combination Tools: Breeding Stacks and Moleculmentioning
confidence: 98%
“…The cost of securing regulatory approval is not only associated with the provision of information on selected events, but the associated indirect costs that are incurred whilst managing product development. For example, in the development of the transgenic products it is necessary to select for, or develop strategies for, (Oltmanns et al. , 2010; Ye et al.…”
Section: The Regulatory Environmentmentioning
confidence: 99%
“…The cost of securing regulatory approval is not only associated with the provision of information on selected events, but the associated indirect costs that are incurred whilst managing product development. For example, in the development of the transgenic products it is necessary to select for, or develop strategies for, (Oltmanns et al, 2010;Ye et al, 2011) generation of simple integration events. As well as the cost of dossier preparation other regulatory costs include physical separation requirements imposed by regulators (though these may be impractical or unnecessary), documentation and inspection requirements during trials, waste disposal and staff training.…”
Section: The Cost Of Regulationmentioning
confidence: 99%
“…A recent study (Oltmanns et al. 2010) demonstrated that starting plant transformation from the A. tumefaciens chromosome could be a way to reduce the portion of transgenic plant lines with vector backbone integrations dramatically, but so far, this procedure to produce Agrobacterium plant transformation strains is laborious and not applicable to the widely used strain A. tumefaciens LBA4404.…”
Section: Confirming the Lack Of Vector Backbonementioning
confidence: 99%